Interhemispheric interactions during sentence comprehension in patients with aphasia. (December 2018) - Chu, Ronald; Meltzer, Jed A.; Bitan, Tali
Abstract: Right-hemisphere involvement in language processing following left-hemisphere damage may reflect either compensatory processes, or a release from homotopic transcallosal inhibition, resulting in excessive right-to-left suppression that is maladaptive for language performance. Using fMRI, we assessed inter-hemispheric effective connectivity in fifteen patients with post-stroke aphasia, along with age-matched and younger controls during a sentence comprehension task. Dynamic Causal Modeling was used with four bilateral regions including inferior frontal gyri (IFG) and primary auditory cortices (A1). Despite the presence of lesions, satisfactory model fit was obtained in 9/15 patients. In young controls, the only significant homotopic connection (RA1-LA1), was excitatory, while inhibitory connections emanated from LIFG to both left and right A1's. Interestingly, these connections were also correlated with language comprehension scores in patients. The results for homotopic connections show that excitatory connectivity from RA1-to-LA1 and inhibitory connectivity from LA1-to-RA1 are associated with general auditory verbal comprehension. Moreover, negative correlations were found between sentence comprehension and top-down coupling for both heterotopic (LIFG-to-RA1) and intra-hemispheric (LIFG-to-LA1) connections. These results do not show an emergence of a new compensatory right to left excitation in patients nor do they support the existence of left to right transcallosal suppression in controls. Nevertheless, the correlations with performance in patients are consistent with some aspects of both the compensation model, and the transcallosal suppression account for the role of the RH. Altogether our results suggest that changes to both excitatory and inhibitory homotopic and heterotopic connections due to LH damage may be maladaptive, as they disrupt the normal inter-hemispheric coordination and communication.